Development of Two-dimensional Analytical Model According to Polarizing Characteristics of the Raman Ranges at Recognition of Nanoparticles of Silver on Polyester Fibers - V.M. Emelyanov; T.A. Dobrovolskaya; S.A. Danilova; О.V. Emelyanovа; K.V. Butov (Журнал нано- та електронної фізики)
Parameters of two-dimensional analytical model of an assessment of crossing of ellipses of distribution at recognition of nanoparticles of colloidal silver are given in polyair fibers on multidimensional correlation components of the Raman ranges with control according to polarizing characteristics. Reliability of recognition of nanoparticles increased more than by 1000 times and was estimated on joint probability of normal distributions of intensivnost of the Raman spectrograms of nanoparticles of silver on polyair fibers depending on longitudinal and cross polarization of laser radiation on all range of a range with the analysis of 9 main peaks.